Asas-Asas dalam Penyelenggaraan Pemerintahan yang Baik untuk Mewujudkan Good Governance - Suwari Akhmaddhian (Universitas Kuningan, 2018)
The purpose of this study is to find out and analyze how the arrangements regarding the principles of good governance in Indonesia. The research method uses a normative juridical approach. The results of the study are found that the arrangements regarding the principles of good governance have been regulated in Law Number 28 of 1999 concerning State Administration that is Clean of Corruption, Collusion and Nepotism, Article 24 of Law Number 6 of 2014 concerning Villages, Article 58 Act Number 23 of 2014 concerning Regional Government and Article 10 of Act Number 30 of 2014 concerning Government Administration. Conclusion that the regulation of the principles of good governance in Indonesia has been very good, the administration of government depends on a shared commitment to run the wheels of government in accordance with the objectives of the state.Keywords: principles of good governance, good governance, governanceAbstrakTujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana pengaturan mengenai asas-asas penyelenggaraan pemerintahan yang baik di Indonesia. Metode penelitian menggunakan pendekatan yuridis normatif. Hasil penelitian yaitu ditemukan bahawa pengaturan mengenai asas-asas penyelenggaraan pemerintahan yang baik sudah diatur dalam Undang-Undang Nomor 28 tahun 1999 tentang Penyelenggaraan Negara yang Bersih Bebas dari Korupsi, Kolusi dan Nepotisme, Pasal 24 Undang-Undang Nomor 6 Tahun 2014 tentang Desa, Pasal 58 Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah dan Pasal 10 Undang-Undang Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan. Simpulan bahwa pengaturan mengenai asas-asas penyelenggraan pemerinthan yang baik di Indonesia sudah sangat baik, penyelenggaraan pemerintahan tergantung komitmen bersama dalam menjalankan roda pemerintahan yang sesuai dengan tujuan bernegara.Kata Kunci: asas-asas penyelenggaraan pemerintahan yang baik, good governance, pemerintahan